Aesthetic and Functional Full Mouth Rehabilitation of a Patient Using Extra Coronal Attachments: a case report - Rayavarapu, Sunil; Teja Varma, N.V.; Budumuru, Anil; Yekula, Prem Sagar; Chinta, Anand; Murru, Kalyan (International Journal of Dental Materials, 2022)
Achieving aesthetic and functional requirements in full mouth rehabilitation using combined fixed and removable dentures is difficult. Strategic diagnosis and treatment planning are required to overcome this challenge. Numerous conventional and cutting-edge treatments can result in successful restorations. One such method of treatment is precision attachment retained partial dentures. Selecting strategic abutments is key to the success of the partial denture. This case report describes full-mouth rehabilitation of maxillary and mandibular arches using fixed and attachment retained cast partial dentures.